Observatory of Illicit Economies in Eastern and Southern Africa (Global Initiative Against Transnational and Organized Crime, 2021)
Illicit flows are a major part of the political and economic landscape of northern Mozambique. In South Africa, the trade in poached abalone and the trafficking of synthetic drug still remain joined today. The impact that heroin capsules have had in Durban in terms of violence, profitability and local demand for heroin. How illicit gold from South Sudan and the Democratic Republic of Congo flows through Uganda
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; conflict / conflito

Social protection during conflict: reflections on Tigray - Sabates-Wheeler, Rachel; Lind, Jeremy (Institute of Development Studies, 2021)
Conflict and an ensuing humanitarian crisis in Ethiopia’s northern Tigray region have led to substantial population displacement and threaten the lives and livelihoods of millions. In a situation where rising needs outstripped preliminary humanitarian responses and where safety net programmes that were purposed for shock-response have been curtailed or stopped functioning altogether, what are the […]
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Rest of the World / Resto do Mundo; L - english / inglês; Social Protection PEA; conflict / conflito; social protection / proteção social

Conflict is the new ‘hazard’ on the social protection block - Sabates-Wheeler, Rachel; Slater, Rachel; Lind, Jeremy; Harvey, Paul; Oosterhoff, Pauline; Faith, Becky; Naess, Lars Otto; Selby, Jan; Roberts, Tony; Longhurst, Daniel; Rohwerder, Brigitte; Collyer, Michael; et al. (Institute of Development Studies, 2021)
Although social protection has the potential to address crises in different ways, the evidence base is thematically and geographically patchy. The Foreign, Commonwealth and Development Office-funded (FCDO)-funded Better Assistance in Crises (BASIC) Research programme aims to inform policy and programming on effective social assistance in situations of crisis, including those experiencing climate-related shocks and stressors, protracted conflict and forced displacement.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Social Protection PEA; conflict / conflito; social protection / proteção social

Ten Conflicts to Worry About in 2021 (ACLED, 2021)
A review of key developments in 2020 with a look toward trends to watch in the coming year.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

The Relationship Between Population Growth, Age Structure, Conflict, and Governance in Sub- Saharan Africa - O’Driscoll, Dylan (Institute of Development Studies, Brighton, UK, 2020)
This report addresses the relationship between population growth, age structure, and conflict in Sub-Saharan Africa (SSA). The literature reviewed for this report presents strong evidence that age structure and population growth matter for conflict. There is particularly strong evidence that points to the relationship between young age structure and conflict, although studies that disaggregate types of conflict and characteristics of young age structures (urban, male, etc.) tend to offer more robust findings. Youth bulges in particular have been associated with increased risk of conflict. The general consensus is that, in countries that will continue to experience high rates of population growth and large youth cohorts, the potential for conflict will continue to be elevated. COVID-19 is putting a dent in already weak formal employment and education. Policy responses to the pandemic will have lasting impacts for those most affected, including young people, and should therefore include them in response. The following policy recommendations are made in the literature including Patriarchal gender norms and masculinity contribute to violence and conflict, and thus policies aimed at increasing gender equality help mitigate conflict risk; The prediction that youth bulge is associated with the onset of conflict should encourage policymakers in countries with young age structures to address societal and economic inequality and foster greater inclusion of the younger cohorts into society; and Youth underemployment (and unemployment) remain an issue in SSA; bringing about structural changes that facilitate the transition into the labor market is likely to mitigate the conflict risks associated with youth bulges
Accepted: 2020-11-04T11:13:17Z Publisher: Institute of Development Studies
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; conflict / conflito; gender / género; youth / juventude

The Islamic State and the crises of COVID 19 - Victoria, Artur (2020)
According to the Homeland Security Today website, the statement lists "guidelines for dealing with the epidemic". For the Islamic State, the main advice is "to trust God and take refuge in Him from disease", but followers have an "obligation" to take protective measures to prevent it. Among these measures, the terrorist group emphasizes that "the healthy should not enter the land of the epidemic and the sick must not leave it". According to the council, terrorists should not travel to Europe and the United States, which are common targets in the West, nor to countries in the Middle East such as Iran, Iraq and Saudi Arabia. The group dominates provinces and has active cells in some countries still free of the disease, such as the Central and West Africa region, as well as Syria and Yemen, where civil war makes it difficult to collect information about epidemics. But cases have already been confirmed in Algeria, Egypt, Iraq, Afghanistan, India, the Philippines and Indonesia. The reorganization in Africa of ISIS - Evolution and progression in Mozambique In Mozambique, according to statements by the President of the Republic and the Minister of Defence, there are groups of terrorists in the district of Cabo Delgado and other groups in the centre, but who are considered to be affected by RENAMO. The situation is complicated because as these groups demonstrate, they show all the characteristics of IS members.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Mozambique: Military maritime cooperation agreement with France under discussion - Lusa (Club of Mozambique, 2020)
Mozambique and France are discussing a military maritime cooperation agreement, a diplomatic source in the European country told Lusa in the context of possible support in the fight against terrorism in Cabo Delgado. "No operational military support has been provided to Cabo Delgado by the French
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Theories of Change for Promoting Empowerment and Accountability in Fragile and Conflict-Affected Settings - Green, Duncan (IDS, 2017)
This paper explores the current state of thinking among a range of aid actors (multilaterals, bilateral, applied scholars and international non-governmental organisations) on how to promote empowerment and accountability in fragile, conflict and violence affected settings. It seeks to identify trends, gaps and weaknesses in that thinking, and propose research questions and hypotheses to test. Three underlying sources of confusion are identified that are hindering progress on both understanding empowerment and accountability in fragile, conflict and violence affected settings, and taking helpful action to promote it. They are: (1) theory of endogenous change (e.g. on how empowerment and accountability arise in situ) versus the theory of action of an external intervention; (2) fragility versus conflict: there is no clear justification for combining these different aspects into a single category; and (3) empowerment versus accountability: donor analysis and practice has been overwhelmingly weighted towards accountability, exhibiting limited understanding or interest in the nature of power.
Accepted: 2017-11-21T13:51:12Z ISSN: 2040-0209
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; conflict / conflito; empowerment / empoderamento; fragility / fragilidade

Power, livelihoods and conflict: case studies in political economy analysis for humanitarian action (Humanitarian Policy Group, Overseas Development Institute, 2003)
What can political economy analysis contribute to humanitarian aid interventions? How can agencies undertake such analysis in difficult environments? This chapter introduces the findings of a study (2001-2002) of four cases: Afghanistan, the eastern Democratic Republic of the Congo (DRC), Sierra Leone and the Casamance in Senegal. Political economy analysis is best conducted alongside existing humanitarian operational activities via integration into existing analytical tools.
OCLC: 717007801
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); conflict / conflito; power / poder

What Happens to the State in Conflict?: Political Analysis as a Tool for Planning Humanitarian Assistance - Cliffe, Lionel; Luckham, Robin (Disasters, 2000)
It is now part of received wisdom that humanitarian assistance in conflict and post-conflict situations may be ineffective or even counterproductive in the absence of an informed understanding of the broader political context in which so-called ‘complex political emergencies’ (CPEs) occur. Though recognising that specific cases have to be understood in their own terms, this article offers a framework for incorporating political analysis in policy design. It is based on a programme of research on a number of countries in Africa and Asia over the last four years. It argues that the starting-point should be an analysis of crises of authority within contemporary nation-states which convert conflict (a feature of all political systems) into violent conflict; of how such conflict may in turn generate more problems for, or even destroy, the state; of the deep-rooted political, institutional and developmental legacies of political violence; and of the difficulties that complicate the restoration of legitimate and effective systems of governance after the ‘termination’ of conflict. It then lists a series of questions which such an analysis would need to ask — less in order to provide a comprehensive check-list than to uncover underlying political processes and links. It is hoped these may be used not only to understand the political dynamics of emergencies, but also to identify what kinds of policy action should and should not be given priority by practitioners.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/1467-7717.00150
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); conflict / conflito; governance / governação

Programming in Fragile and Conflict-Affected Countries: Programme policy guidelines (Oxfam)
There is no single prescriptive approach to working in fragile and conflict-affected contexts. The underlying causes of problems and the dynamics of such contexts are too complex and unpredictable for that. There is a great diversity of underlying causes, actors, needs, opportunities, and responses. Staff are faced with immense challenges and work under greater limitations […]
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; conflict / conflito; government policy / politica governamental